Evaluation of Antidiabetic Property of Sansevieria liberica Gerald and Labroy (Dracaenaceae) Leaf Using Alloxan Induced Diabetes Model (Nigerian Journal of Pharmaceutical Research, 2021)
Background: The phytochemical screening and antidiabetic activities of the methanol leaf extract and fractions of Sansevieria liberica Ger. and Labr. were investigated.Objectives: To identify the phytoconstituents present and evaluate the anti-diabetic activity of the leaf of S. liberica Ger. and Labr.Material and Methods:  A 1.2 g of the pulverized leaf was cold macerated in methanol to obtain 240 g of the crude extract (CE), fractionation was done using n-hexane, ethylacetate and butanol. The CE and the fractions were screened for phytochemical and antidiabetic analysis using standard procedures. Diabetes was induced by intraperitonial injection of alloxan. The blood glucose levels were analyzed as indices of diabetes. Results:  After 24 hours, alloxan increased the blood glucose level of rats indicating hyperglycaemia.  Treatment of the rats with the extract and fractions reduced the blood glucose level within 3 to 7 days of treatment. The standard antidiabetic, metformin (500 mg/kg) also showed similar effect. Extracts (250 and 500 mg/kg) of the crude extract decreased significantly (p n-Hexane fraction > butanol fraction. The phytochemical screening of the extract and fractions revealed the presence of flavonoids, steroids, alkaloids, glycosides etc.Conclusions: From the findings, S. liberica leaf posses antidiabetic activity which may be due to the phytochemical constituents present, and this justifies its use by local users as traditional remedy for diabetes mellitus.